Light-responsive prodrug-based supramolecular nanosystems for site-specific combination therapy of cancer - Phua, Fiona Soo Zeng (2020)
On-demand release of chemotherapeutic drugs from their prodrugs triggered by light irradiation has been attracting great attention for effective cancer treatment. Herein, we prepared prodrug based supramolecular nanoparticles (HA−aPS−aCPT) composed of (1) β-cyclodextrin conjugated hyaluronic acid polymer (HA−CD), (2) adamantane-modified camptothecin prodrug (aCPT) caged via reactive oxygen species (ROS) responsive thioketal linker, and (3) adamantane modified photosensitizer (aPS), for combination photodynamic therapy and light-controlled chemotherapy. aCPT could release free camptothecin by the cleavage of ROS-sensitive thioketal linker. aPS is employed to produce ROS under light irradiation. HA−aPS−aCPT nanoparticles are formed by supramolecular means with excellent colloidal stability and monodispersity in aqueous solution. Confocal imaging and flow cytometric analysis confirm the selective uptake of HA−aPS−aCPT nanoparticles via CD44 receptor-mediated endocytosis by MDA-MB-231 cells, on account of the targeting capability of hyaluronic acid. Cell viability assays show that HA−aPS−aCPT nanoparticles possess minimal cytotoxicity in the dark, while presenting high cellular toxicity under light irradiation. In vivo experiments exhibit selective accumulation of HA−aPS−aCPT nanoparticles in MDA-MB-231 tumor of nude mice. Significant tumor regression is observed when light irradiation is applied after intravenous injection of HA−aPS−aCPT nanoparticles. Thus, HA−aPS−aCPT nanoparticles demonstrate a great potential for on-demand combination photodynamic therapy and chemotherapy of tumor.